2022
DOI: 10.1101/2022.12.21.521473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activated gliosis, accumulation of amyloid β and hyperphosphorylation of tau in aging canines with and without cognitive decline

Abstract: Canine cognitive dysfunction (CCD) syndrome is a well-recognized naturally occurring disease in aged dogs, with a remarkably similar disease course, both in its clinical presentation and neuropathological changes, as humans with Alzheimers disease (AD). Similar to human AD patients this naturally occurring disease is found in the aging canine population however, there is little understanding of how the canine brain ages pathologically. It is well known that in neurodegenerative diseases, there is an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A prospective longitudinal study of older cardiac surgery patients found that the prevalence of dementia 7.5 years after interventions was significantly higher than the population prevalence [12]. Animal studies also indicate that surgery and anesthesia contribute to cognitive decline and AD-associated neuropathologic changes, including neuroinflammation, Aβ aggregation, and tau hyperphosphorylation [30,31].…”
Section: Pocd Risk Factors and Clinical Effectsmentioning
confidence: 99%
“…A prospective longitudinal study of older cardiac surgery patients found that the prevalence of dementia 7.5 years after interventions was significantly higher than the population prevalence [12]. Animal studies also indicate that surgery and anesthesia contribute to cognitive decline and AD-associated neuropathologic changes, including neuroinflammation, Aβ aggregation, and tau hyperphosphorylation [30,31].…”
Section: Pocd Risk Factors and Clinical Effectsmentioning
confidence: 99%
“…Dogs also exhibit age-related amyloid plaque pathology, neuroinflammation, and neurodegeneration, making them particularly suitable for studying anti-AD therapy. 72 A study using middle-aged beagles found protective effects of one-year tacrolimus treatment against age-and AD-related brain microstructural changes, as measured by higher-order diffusion magnetic resonance imaging (MRI) metrics. The authors found that long-term and low-dose administration of tacrolimus reduced the neurite density index (NDI), detected inflammation as cellular edema results in increased volume without increased orientation dispersion index (ODI), a diffusion metric positively correlated with microglial density in hippocampal and parahippocampal gyri of experiment animals.…”
Section: Age-associated Animal Brains and Other Models Using To Answe...mentioning
confidence: 99%
“…Canines possess a metabolic system that closely resembles that of humans. Dogs also exhibit age‐related amyloid plaque pathology, neuroinflammation, and neurodegeneration, making them particularly suitable for studying anti‐AD therapy 72 . A study using middle‐aged beagles found protective effects of one‐year tacrolimus treatment against age‐ and AD‐related brain microstructural changes, as measured by higher‐order diffusion magnetic resonance imaging (MRI) metrics.…”
Section: Effects Of Can and Cni On Brain Pathology Mitochondrial Func...mentioning
confidence: 99%